Combined cooling and power cycle for engine waste heat recovery using CO2-based mixtures. (1st February 2022) - Yao, Yu; Shi, Lingfeng; Tian, Hua; Wang, Xuan; Sun, Xiaocun; Zhang, Yonghao; Wu, Zirui; Sun, Rui; Shu, Gequn
Abstract: CO2 -based mixture is a potential working fluid choice of combined cooling and power cycle (CCP) due to its superior thermodynamic performances and the removal of the limit of CO2 critical temperature. This study proposes a CCP system using CO2 -based mixtures, loaded on a refrigerated truck, to realize multi-mode transformations for diverse cooling and power demands. The components of mixtures are strictly screened and key parameter analyses and optimization in terms of energy, exergy, adjustability, and economic performance are conducted to find the general laws and the best composition of the mixtures. The results show CO2 -based mixtures have better energy-saving potential, adaptability, adjustability, and compactness than CO2 . By comparison, CO2 /R32 is recommended for superior output capacity, lower operation parameters, remarkable adjustability, and cheaper investment cost. CCP using CO2 /R32 can maximally achieve 6.9% power enhancement or 5.9 times cooling enhancement relative to the refrigerated truck using a stand-alone refrigerator, and 19% power increase or 80% cooling increase relative to the CO2 system. It can realize smooth and steady mode transformation to achieve complex and diverse allocation of refrigeration and power in actual operation. Graphical abstract: Image 1 Highlights: A combined cooling and power cycle using CO2 -based mixtures with multi-mode operation is proposed. A variety of mixtures are screened to find the best working fluid suitable for the cogeneration system. The CO2 -based mixtures improve the environmental adaptability and thermodynamic performances relative to pure CO2 . CO2 /R32 shows the outstanding output capacity, adjustability and economic performance through parameter optimization.